“Panoptic na Pag-unlad”? On the Perils and Potentials of “Smart” Urbanism in Manila - Theriault, Noah (Archīum Ateneo, 2023)
In Manila proponents of smart urbanism offer solutions to daunting urban problems in the form of remote sensing, artificial intelligence, and digital mass communication. Thisarticle puts these proposals into theoretical and historical context and asks what it means to be a “smart city” amid a resurgence of authoritarianism in the Philippines and around the world. By putting the principles of science and technology studies in dialogue with those of critical urban geography, our analysis foregrounds the tensions between the generative potentials of “patuloy na pag-unlad” (continuous development) and the panoptic impulses of authoritarian capitalism.KEYWORDS: SMART CITIES • URBAN HISTORY • CRITICAL GEOGRAPHY • SCIENCE AND TECHNOLOGY STUDIES • NEW CLARK CITY